2021
DOI: 10.5114/ceh.2021.109225
|View full text |Cite
|
Sign up to set email alerts
|

Liver function test abnormalities in COVID-19 patients and factors affecting them – a retrospective study

Abstract: Aim of the study: We aimed to study liver function test abnormalities in our COVID-19 patients and factors affecting them and to evaluate whether liver function test abnormalities are related to the severity of COVID-19. Material and methods: Our retrospective study included 118 patients who were SARS-CoV-2 positive. Their median age was 40 years. Fifty percent were male. Clinical and biochemical data were collected from patient records during the period from the start of June 2020 to the end of July 2020. Liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the case of damage to the liver and other organs involved in the removal of modified albumin, high amounts of AOPPs-HSA and ALEs-HSA may not be cleared from the bloodstream as quickly as they would be in a healthy person. Liver function test abnormalities are very common in COVID-19-related pneumonia patients [ 92 , 97 , 98 ]. This may be related to liver injury by the virus itself, inflammatory responses, hepatic ischemia, hepatic hypoxia, or even tissue damage and muscle breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of damage to the liver and other organs involved in the removal of modified albumin, high amounts of AOPPs-HSA and ALEs-HSA may not be cleared from the bloodstream as quickly as they would be in a healthy person. Liver function test abnormalities are very common in COVID-19-related pneumonia patients [ 92 , 97 , 98 ]. This may be related to liver injury by the virus itself, inflammatory responses, hepatic ischemia, hepatic hypoxia, or even tissue damage and muscle breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Wang et al, 2021, that revealed elevated AST levels as its percentage recorded (33.3%) in COVID-19 infected patients and also elevated ALT (24.1%). 32 The study by Cai et 36 According to lipid profile our results showed that the level of TG was elevated in serum of COVID-19 infected patients, however, there was no significant difference between COVID-19 infected patients and the control group. This result is similar to that reported by Shahab et al, 2022, who showed no significant difference appeared in TG levels among the studied groups.…”
Section: Discussionmentioning
confidence: 72%
“…The top enriched metabolic terms are given in the form of a volcano plot in Figure 5 B, and primarily involve processes commonly associated with viral infection and multiplication, such as RNA processing, cell cycle phases and metabolite/amino acid processing. The top associated disease terms are given in Figure 5 C. Notably, these include pathological conditions that have been directly related to COVID-19, such as respiratory function loss [ 62 ], decreased liver function [ 63 ], and lower limb weakness [ 64 ]. In addition, the analysis highlighted diseases that have been found to result in complications when coupled with COVID-19, such as Diamond–Blackfan anemia [ 65 ] and neurogenic muscular atrophy [ 66 ].…”
Section: Resultsmentioning
confidence: 99%